LIBERALIZATION AND MARKET CONCENTRATION IN THE INSURANCE INDUSTRY: CASE OF CROATIA - Lorena Škuflić; Fran Galetić; Branimir Gregurić (Economic Review)
This paper analyzes market concentration on the market of insurance companies in Croatia. For a very long time, Croatian insurance market was dominated by one company. After the liberalization, the number of insurance companies on the market began to increase, which led to a significant fall in levels of market concentration. The paper analyzes various indicators of market concentration, and for each indicator there is a calculated value which should help to see the trend. From all the analyzed indicators of market concentration, three were selected for the estimation of econometric models trend. The aim of these models is to predict the movement of market concentration on the insurance market in the next few years. The analysis shows that in the near future we can expect a further reduction in the level of concentration on Croatian insurance market companies, as well as the transition to less concentrated market structures.